Axial Length and Ocular Development of Premature Infants without ROP. (15th October 2017) - Zha, Yi; Zhu, Guangdong; Zhuang, Jinfei; Zheng, Haihua; Cai, Jianqiu; Feng, Wangqiang
Abstract : Purpose . To investigate the ocular parameters of premature infants without ROP at gestational age (GA) more than 28 weeks and their relationship with growth parameters. Methods . 76 preterm infants without ROP and 65 term infants were involved to undergo portable slit lamp, RetCam3, ultrasonic A-scan biometry, and cycloplegic streak examination at their 40 weeks' postconceptional ages (PCA). Ocular parameters of infants' right eye and growth parameters were used for analysis. Results . All the infants were examined at 40 weeks' PCA. No significant difference was found between male and female in axial length of preterm infants ( p  = 0.993) and term infants (p = 0.591 ). Significant differences were found in axial length (AL), anterior chamber depth (ACD), lens thickness (LT), and vitreous depth (VD) between preterm and term infants. No significant correlation was found between AL and spherical equivalent in preterm infants' group. In preterm group, AL was significantly correlated with gestational age (GA), birth weight (BW), and head circumference (HC). Conclusions . Preterm infants had shorter AL, shallow ACD, thicker LT, and thinner VD compared to term infants. Refractive error in preterm infants at GA between 28 to 37 weeks was not related to axial length. Among all the growth parameters of preterm infants, GA, BW, and HC had effect on axial length.